Is Alzhezimer’s disease a New Type Diabetes? Crosstalk between two serious disorders: review - Dobosz, Maciej; Rudziński, Gracjan; Chilimoniuk, Zuzanna; Więsyk, Piotr; Kusak, Natalia; Chałupnik, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction and purpose: More and more reports suggest that diabetes plays an important role in the pathogenesis of Alzheimer's disease (AD). Understanding this link may provide a new approach to modulating the onset and progression of sporadic AD cases. The aim of the study is to present the current state of knowledge on the basic mechanisms and factors influencing the development of AD in patients with type 2 diabetes in the context of clinical practice. State of knowledge: It is estimated that up to 80% of Alzheimer's patients have glucose intolerance or diabetes. Impaired insulin signaling can lead to abnormal processing and accumulation of beta-amyloid protein, which can result in memory deficits and cognitive decline. Insulin deficiency can also cause over-activity of the GSK3 enzyme, leading to tau hyperphosphorylation and senile plaque accumulation. Diabetes can also cause fibrotic changes in cerebral vessels, disrupting brain metabolism and potentially leading to hippocampus atrophy. The release of cytokines during the metabolic syndrome can also cause oxidative stress and neuroinflammation, which may contribute to neuronal atrophy. It has been reported that healthy diet, physical exercises and prevention of metabolic diseases may reduce the incidence of AD. Conclusions: Epidemiological data and pathophysiological studies indicate a significant relationship between these diseases that AD is sometimes called Type 3 diabetes. Early detection of hyperglycemia and its proper management, may be crucial in the context of the clinical prevention of dementia diseases. It is essential to pay attention to the cognitive abilities of patients with metabolic diseases.